Smallholder Farmers' Perception of Climate Change Resilience in the Bosome Freho District Assembly in the Ashanti Region, Ghana (Ghana Journal of Science, Technology and Development, 2023)
Climate change and resource depletion disproportionately affect smallholder farmers and rural poor. Droughts, storms, for example, strain the ecosytems they rely on for sustenance. The reserach aimed to evaluate smallholder farmers perceptions of climate change and resilience in the Boasome Freho district. Descriptive surveys, questionnaire, focus group discussions (FDGs) and in-depth interviews were used in data analysis. Respondents included 160 smallholder farmers, four agricultural extension officerss, and four chief farmersfrom the localities.  Dta analysis werePerformed  with SPSS version 23.0. According to the survey, most smallholder farmers are consciuos of the effects of climate changes, such as lower agricutiral output, extreme weather events, rising temperature, and pest and crop invasion. The study discovered that the farmers prIpmary sources of climate data are media, neighbours(older farmers), and agricultural extension officers. The paper found that farmers adaptation and resillence to the effects of climate change were generally high. Crop diversification, changing planting dates, changing crops, irrigation, planting short-season varieties, finding off-farm jobs and reducing farm size are all effective adaptive tactics for most farmers. The researcher suggests that the Ghana meteorological agency provide clamte-related information to the district directorate of agriculture. The Ministry of Food and Agriculture( MOFA) should sensitise smallholder farmers on specific climate -smart agrictcitural practices.